Africa's Contextual Realities Foundation for the Church's Holistic Mission - Nkansah-Obrempong, James (2017)
This article discusses Africa's contextual realities and argues why these realities should inform the church's mission agenda. The article explores the nature, role, and purpose of the church. It argues that the church is people. It is made up of the community of God's people, who have been reconciled to God through the atoning death of Jesus Christ. They are salt and light to the world. The characterization of the church as salt and light relates to the church's mission. The church's mission, the article argues, is summed up in the Great Commission in Matthew 28:19-20 and the Great Commandment in Mark 12:30-31. The mission of the church, therefore, has a dual purpose: outreach and social responsibility or service. Both are critical for the church's mission activities. Giving the contextual realities in Africa, the article asserts the mission of the church in Africa must be holistic to address effectively the needs of the continent. The article asserts this mission model has its grounding in the scriptures. It further argues that the mission of the church is grounded in and determined by God's mission in the world. God's approach to mission was holistic. Furthermore, this was the mission model Jesus and the apostles used. The article suggests integral or holistic mission for the church's mission agenda if it wants to see transformation in Africa. The article concludes that using an integral or holistic approach will help the church to address the many challenges - moral, spiritual, material, psychological, and emotional - facing humanity and the world today. That way, the church will fulfil the three-fold mission approach of Jesus: evangelism or outreach; discipleship; and service to humanity and God's creation. In doing this, the church will glorify God.
Keywords: Discipleship; Great Commission; Holistic Mission; Integral Mission; Lausanne Movement; Outreach; Transformation